Annexin 1 localisation in tissue eosinophils as detected by electron microscopy - Sonia M. Oliani; Amilcar S. Damazo; Mauro Perretti (Mediators of Inflammation)
Background: Human and rodent leukocytes express high levels of the glucocorticoid-inducible protein annexin 1 (ANXA1) (previously referred to as lipocortin 1). Neutrophils and monocytes have abundant ANXA1 levels.